Ethnomathematics in Sidoarjo Batik Motifs: An Ethnographic Study of Mathematical Concepts in Local Cultural Artifacts - Fitriyah, Nur; Wiryanto; Ekawati , Rooselyna; Mariana, Neni; Siswono, Tatag Yuli Eko (Papanda Publisher, 2025)
This study explores the integration of mathematical concepts within the traditional batik motifs of Sidoarjo, Indonesia, through a qualitative ethnographic approach. Focusing on three selected motifs—Beras Wutah, Kembang Tebu, and Udang Bandeng—the research aims to identify and describe inherent mathematical elements such as symmetry, geometry, patterns, and proportional reasoning embedded in the design and production process. Data were collected through direct observation, semi-structured interviews with local batik artisan Ir. Nurul Huda, and documentation analysis at the Batik Tulis Al-Huda Gallery in Sidokare, Sidoarjo. The data were analyzed using Spradley’s ethnographic method, which includes domain, taxonomic, and componential analysis. Findings reveal that Sidoarjo batik motifs are rich in mathematical structures. The Beras Wutah motif displays tessellation and reflective symmetry; Kembang Tebu illustrates rotational symmetry and repetitive geometric patterns; while the Udang Bandeng motif incorporates proportional scaling and spatial reasoning. These mathematical ideas, though traditionally unformalized, demonstrate deep-rooted local knowledge that aligns with formal mathematical principles. The integration of ethnomathematical perspectives into classroom instruction has the potential to contextualize learning, enhance students’ engagement, and foster cultural appreciation. This study concludes that batik, as a cultural artifact, holds significant educational value in mathematics education. Incorporating local cultural resources like batik into curriculum design not only supports culturally responsive teaching but also bridges abstract mathematical concepts with tangible real-world experiences. The findings advocate for the inclusion of ethnomathematics in primary education as a strategy to make mathematics more accessible, meaningful, and inclusive for diverse learners.